American GI Forum 1995 - San Jose Queen Coronation Rehearsal (and Other Events) - Castellano, Alcario:::creator:::::::::::: (2024)
Video and transcripts of the 1995 American GI Forum - San Jose chapter Queen coronation rehearsal. Also includes an American GI Forum meeting led by Abel Cota (52:48), a home video shot by Alcario Castellano (57:49), and a children's dance recital in Sunnyvale, California (1:07:30).